Deep learning and optical coherence tomography in glaucoma: Bridging the diagnostic gap on structural imaging - Thompson, Atalie C.; Falconi, Aurelio; Sappington, Rebecca M. (Frontiers in Ophthalmology, 2022)
Glaucoma is a leading cause of progressive blindness and visual impairment worldwide. Microstructural evidence of glaucomatous damage to the optic nerve head and associated tissues can be visualized using optical coherence tomography (OCT). In recent years, development of novel deep learning algorithms has led to innovative advances and improvements in automated detection of glaucomatous damage and progression on OCT imaging. DL algorithms have also been trained utilizing OCT data to improve detection of glaucomatous damage on fundus photography, thus improving the potential utility of color photos which can be more easily collected in a wider range of clinical and screening settings. This review highlights ten years of contributions to glaucoma detection through advances in deep learning models trained utilizing OCT structural data, and posits future directions for translation of these discoveries into the field of aging and the basic sciences.